Cellular Photostimulation with Hydrogen-bonded Organic Semiconductor Microcrystal Interfaces - Jakešová, Marie (Jihočeská univerzita, 2017)
The aim of this thesis was to investigate the potential use of hydrogen-bonded organic semiconductors in photostimulation of mammalian cells and the determination of the mechanism thereof.
Cellular Photostimulation with Hydrogen-bonded Organic Semiconductor Microcrystal Interfaces
Keywords: semiconductor; photostimulation; electrophysiology; microcrystal; semiconductor; photostimulation; electrophysiology; microcrystal